Investigating the drivers and barriers to implementing green building features and initiatives (GBFIs) in South Africa's private residential housing sector - Madzingaidzo, Raphael (Department of Construction Economics and Management, 2025)
The construction industry has long been criticised for being a significant contributor to global carbon emissions and a large consumer of energy. Economies around the world, however, have taken an active role in addressing the construction industry's carbon footprint and high energy demands by incorporating green technologies and practices in construction projects. Over the years, Green Building Features and Initiatives (GBFIs) have provided a solution to the construction industry's challenges, particularly in the building sector which is a notable consumer of energy. The Green Building Council of South Africa (GBCSA) manages and applies tools such as Green Star, EDGE, and Net-Zero to assist in the incorporation and certification of GBFIs in buildings. The study seeks to identify the drivers and barriers of implementing GBFIs in South Africa's private residential sector. A literature review was conducted to identify key drivers and barriers for the adoption of GBFIs from a global perspective. The study employed a qualitative research approach comprising multiple case study analysis, where semi-structured interviews were conducted with key stakeholders in the construction industry. The case studies (limited to South Africa) involved five major residential developments in municipalities located in the Western Cape and Gauteng provinces. The study highlighted socio-cultural factors such as client awareness, enhanced standard of living, and developer initiative as being the key drivers to the adoption of GBFIs, followed by increased international investment. However, the study yielded numerous barriers, with key barriers being government related barriers in the form of inadequate renewable energy (RE) green building regulations and low levels of municipal involvement; followed by human related barriers in the form of a lack of education concerning GB principles and practices by construction stakeholders; and lastly market related barriers in the form of high financial cost of RE generation. The study identified key strengths and weaknesses of the green building rating tools that in turn contribute to the drivers and barriers. This study adds to the existing literature pertaining to GBFIs by providing insight within the context of the private residential property sector in a developing country.